Biskuit Garut-Tempe Tinggi Energi Protein sebagai Alternatif Snack untuk Anak Usia Sekolah; Analisis Kandungan Energi Protein dan Daya Terima - Evitha Latifah; Setyaningrum Rahmawaty; Rusdin Rauf (University of Darussalam Gontor, 2019)
One of nutrition problems in school-age children is protein energy malnutrition (PEM). This can be solved with provision a high energy protein contained snack using local food such as arrowroot and tempeh. The aims of research is to formulate biscuit arrowroot-tempeh that acceptable for school-age children. The research was conducted into 5 steps, namely 1) formulation of biscuit arrowroot-tempeh, 2) biscuit production, 3) determination of energy content, 4) protein content analysis and, 5) organoleptic test on 30 school childrenaged 9-12 yo. Formulation ratios of the arrowroot flour and tempeh flour for biscuit productions were80:20 (biscuit A), 75:25 (biscuit B) and 70:30 (biscuit C). Energy (kkal)/protein(g/100g) contents of biscuitsA, B and C were 868,803/6,15; 876,299/6,95 and 883,796/8,35, respectively.Biscuit A was the most preffered biscuit among school children aged 9-12 yo. Biscuits arrowroot-tempeh can be used as an healthy high energy protein snack for school-age children.